Immunological Profile and Predisposition to Autoimmunity in Girls With Turner Syndrome - Gawlik, Aneta Monika; Berdej-Szczot, Elzbieta; Blat, Dorota; Klekotka, Renata; Gawlik, Tomasz; Blaszczyk, Ewa; Hankus, Magdalena; Malecka-Tendera, Ewa (Frontiers in Endocrinology, 2018)
Objective: The risk of autoimmune diseases (AD) in patients with Turner Syndrome (TS) is twice higher than in the general female population and four times higher than in the male population. The causes of the increased incidence of AD in TS are still under discussion. We hypothesised the presence of a specific humoral, cellular and regulatory T cell (Treg) immunity profile which predisposes to autoimmune diseases, disorders of immunity and disorders of immune regulation. Methods: The study encompassed 37 girls with TS with no signs of infection. The control group included 11 healthy girls with no hormonal disorders. A medical history focused on AD and immunity disorders was taken from all participants. The levels of: immunoglobulins IgG, IgA, IgM, total lymphocytes, lymphocytes subpopulations CD3+, CD4+, CD8+, CD19+, natural killer cells, Treg cells (CD4+CD25+CD127-FOXP3+), anti-inflammatory cytokines (IL-10, TGFβ), anti-nuclear antibodies (ANA), glutamic acid decarboxylase (GAD65 Abs), anti-thyroid peroxidase (anti-TPO Ab) and anti-thyroglobulin (anti-TG Ab) autoantibodies were determined in each participant. Results: The mean age and BMI in the TS group and in controls were comparable (11.9±4.1 vs. 12.5±4.0 yrs.; 19.2±3.4 vs. 19.7±4.6, p>0.05). Mean hSDS was significantly higher in controls (-2.2±0.9 vs. -0.4±1.5, p<0.0001). AD and recurrent otitis media with complications were previously confirmed in 9(24.3%) and 10(27.0%) girls with TS. The TS group had significantly lower levels of IgG (p=0.02), lower %CD4 (p<0.001) and a significantly lower CD4:CD8 ratio (p<0.001). There were no differences in mean Treg% between the groups. However, comparing Treg% between the TS group with coexisting autoimmunity and the remaining participants, a statistically significant difference was observed (2.09±0.5 vs. 2.77±1.6, p=0.048). Patients with iXq had lower CD4% and more frequently had positive anti-TPO Ab and anti-TG Ab compared to the remaining TS girls and controls (p=0.001, p<0.001, p=0.01). Conclusions: TS predisposes to AD, especially if associated with coexisting iXq. Our preliminary results show that patients with TS may present a specific profile of humoral and cellular immunity markers, different from healthy girls.